The Role of the Ma'nā Maghzā Approach and Maqāshidī Tafsir in Efforts to Contextualize the Meaning of the Qur'an in the Contemporary Era - Aulia Nisaa'i Rosyida; Andri Nirwana AN; Rezaul Islam (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: The purpose of this study is to explore and deepen the understanding of the ma'nā--maghzā approach introduced by Sahiron Syamsuddin, as well as to examine its effectiveness in understanding the verses of the Qur'an by the development of the current context. Theoretical framework: This research refers to a contextual hermeneutic approach that balances between textual meaning and contextual interpretation, particularly in the realm of modern interpretive studies. Literature review: this research covers various methods of interpretation, such as Tafsir Maqashidi and the ma'nā--maghzā approach, each of which focuses on understanding the purpose of sharia (maqashid al-shari'ah) and its contextual and socially relevant meaning. Methods: The method used in this study is qualitative-descriptive, with textual analysis of Qur'anic verses and a study of contemporary interpretive approaches. Results: The results of the study show that the ma'nā--maghzā and maqashidi approaches are able to present a more applicable and contextual understanding of the Qur'an, and become a method that is increasingly in demand among Indonesian academics. Implications:  This study highlights the need to strengthen contextual approaches in the study of interpretation to answer the challenges of the times and bridge the gap between texts and social realities. Novelty: this research lies in the emphasis on the contribution and relevance of the ma'nā--maghzā approach in the framework of modern Indonesian interpretation and its synergy with the maqashidi approach that has been developing in the study of ushul fiqh.